Naturally light invisible axion in models with large local discrete symmetries - Dias, Alex G.; Pleitez, V. [UNESP]; Tonasse, M. D. (American Physical Society (APS), 2003)
We show that by introducing appropriate local [Formula Presented] symmetries in electroweak models it is possible to implement an automatic Peccei-Quinn symmetry, at the same time keeping the axion protected against gravitational effects. Although we consider here only an extension of the standard model and a particular 3-3-1 model, the strategy can be used in any kind of electroweak model. An interesting feature of this 3-3-1 model is that if we add (i) right-handed neutrinos, (ii) the conservation of the total lepton number, and (iii) a [Formula Presented] symmetry, the [Formula Presented] and the chiral Peccei-Quinn [Formula Presented] symmetries are both accidental symmetries in the sense that they are not imposed on the Lagrangian but are just a consequence of the particle content of the model, its gauge invariance, renormalizability, and Lorentz invariance. In addition, this model has no domain wall problem. © 2003 The American Physical Society.